THE INFLUENCE OF REWARD AND PUNISHMENT ON THE PERFORMANCE OF AVIATION SECURITY PERSONNEL AT EL TARI KUPANG AIRPORT - Muthia Devi, Mahatanti; Fatimah, Siti; Maharani Sukma, Meita (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
El Tari Kupang Airport plays a strategic role in supporting air transportation in East Nusa Tenggara. Aviation Security personnel are expected to work optimally to ensure flight security. This study aims to analyze the influence of reward and punishment on the performance of Aviation Security personnel at El Tari Kupang Airport. The study uses a quantitative method with a causal associative approach. Data collection was conducted through questionnaires distributed to 62 respondents and supported by documentation. Data analysis involved validity, reliability, normality tests, and multiple linear regression using SPSS version 26. The results show that reward has a positive and significant effect on personnel performance with a regression coefficient of 1.415 and a significance value of 0.000. Punishment also shows a positive and significant effect with a coefficient of 0.888 and a significance value of 0.000. The conclusion is that the implementation of appropriate rewards and firm punishments can improve the performance of Aviation Security personnel.